Estudo do modelo de Rabi no contexto de sistemas quânticos abertos - Oliveira, Thiago Werlang de (Universidade Federal de São Carlos, 2009)
The Rabi Hamiltonian describes the interaction between a two-level atom and a single mode of the quantized electromagnetic field. In this work we study numerically and analytically the dynamics of the Rabi hamiltonian subjected to damping and dephasing reservoirs, included via the usual Lindblad superoperators in the master equation. When the system is subjected to the Markovian atomic dephasing reservoir, the anti-rotating term in the Rabi hamiltonian leads to a linear photon generation from the vacuum. In the case where the dissipation effects are present, the asymptotic mean photon number attains a value higher than the thermal photon number, expected in the absence of the anti-rotating term. We reveal the origins of the phenomenon and estimate its importance in realistic situations. Still, we evaluate approximately the photon creation rate in the pure dephasing case and the asymptotic mean photon number and the atomic population inversion in the general case.
Keywords: Sistemas quânticos abertos; Hamiltoniano de Rabi; Interação da radiação com a matéria; Decoerência (Decoherence); Efeito Casimir dinâmico; Ótica quântica; CIENCIAS EXATAS E DA TERRA::FISICA